Art, Life and Media Merge - Sorensen, Vibeke (Lumina, 2017)
In this essay, we look at some of the principal issues raised by advancements in digital technology in the light of global issues today, reflecting on our engagement with these issues through a range of artworks, from the 1970s to projects in progress. The works explore the potential of art to catalyze harmonious relations between life on earth and emerging technologies, in diverse fields such as digital multimedia and animation, interactive architectural installation, networked visual-music, plant-human interaction and ecology, social media, health and well-being, and wearable transmedia technologies. In these interactions, the artworks foreground our individual and collective experiences of interconnectedness, in our associations with technology as well as in our common interests and concerns as living species. They are based on an understanding of art as an essential form of mental and physical communication, and arise out of a deep concern — for the future of human and all other forms of life, and for the future of the planet. Through these reflections, the essay argues for and stresses the need for a responsible, ethical, humanistic, compassionate, and environmentally conscious approach to art and life in the Anthropocene.